PENGEMBANGAN MODEL PEMBELAJARAN TPS BERBASIS AfL MELALUI PENILAIAN TEMAN SEJAWAT UNTUK PEMBELAJARAN MATEMATIKA PADA POKOK BAHASAN SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SMP/MTS SE-KABUPATEN MAGELANG TAHUN PELAJARAN 2013/2014 - Putra Adi Wibowo; Budiyono Budiyono; Sri Subanti (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of the research were to find out: (1) how the process and the product of an AfL-based TPS learning model development were through peer assessment, (2) which learning model provided better learning outcome, the AfL-based TPS through peer assessment or the TPS one, (3) which students had better learning outcome, those with high, those with moderate or those with low learning independency, (4) in each learning model, which students had better learning outcome, those with high, those with moderate or those with low learning independency, and (5) in each category of learning independency, which learning model provided better learning outcome, the AfL-based TPS through peer assessment or the TPS one. This research was divided into two stages. The first one was learning model development belonging to research and development research. This stage included material collection, model prototype designing, model tryout, and model establishment. The tryout was conducted in four learning. The second was model effectiveness test belonging to a quasi-experimental research with a 2x3 research design. The population was the first semester VIII graders of SMP/MTs (Junior High Schools/Islamic Junior High Schools) throughout Magelang Regency in the school year of 2013/2014. The sampling technique used in this research was stratified cluster random sampling. The sample of research consisted of 138 students: 68 for the experiment 1 class and 70 for the experiment 2 class. Considering the result of hypothesis testing, the following conclusions could be drawn. (1) The AfL-based TPS learning model through peer assessment could be applied at SMP/MTs level in Magelang Regency. (2) The learning outcome of the students treated with AfL-based TPS learning model through peer assessment was better than that of those treated with the TPS one. (3) The learning outcome of students with high learning independency was better than that of those with moderate and low one. The learning outcome of the students with moderate learning independency was as good as that of those with low one. (4) In both the AfL-based TPS learning model through peer assessment and the TPS, the learning outcome of students with high learning independency was better than that of those with moderate and low one, but that of the students with moderate learning independency was as good as that of those with low one. (5) In high, moderate, and low categories of learning independency, the learning outcome of the students treated with AfL-based TPS learning model through peer assessment was better than that of those treated with the TPS one.Keywords: Think Pair Share (TPS), Assessment for Learning (AfL), Peer Assessment, Student Learning Independency.